2010
DOI: 10.1007/s10238-010-0119-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete correction of anemia by erythropoiesis-stimulating agents is associated with insulin resistance in hemodialysis patients

Abstract: Insulin resistance and anemia secondary to erythropoietin deficiency characterize patients with end-stage kidney disease. In a cross-sectional analysis, we examined the relationship between erythropoietin-mediated correction of anemia and insulin sensitivity in nondiabetic hemodialysis patients. Insulin sensitivity (euglycemic-hyperinsulinemic clamp) and endogenous glucose production (primed-continuous infusion of [6,6-(2)H(2)]glucose) were determined in two groups of patients with normal hemoglobin (n:8; mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, EPO therapy for 2 mo decreased PC-1 activity, and this effect was associated with an improvement in IR in hemodialysis patients treated with this drug (194). While partial correction of anemia has a favorable effect on IR, complete correction of anemia by EPO treatment worsens IR in dialysis patients (20). Iron deficiency is associated with activation of hypoxia-inducible factor-1-alpha (HIF-1␣), which stimulates glucose transporters and glycolytic enzyme synthesis as an adaptive response to relative hypoxia (13).…”
Section: Reviewmentioning
confidence: 98%
“…Interestingly, EPO therapy for 2 mo decreased PC-1 activity, and this effect was associated with an improvement in IR in hemodialysis patients treated with this drug (194). While partial correction of anemia has a favorable effect on IR, complete correction of anemia by EPO treatment worsens IR in dialysis patients (20). Iron deficiency is associated with activation of hypoxia-inducible factor-1-alpha (HIF-1␣), which stimulates glucose transporters and glycolytic enzyme synthesis as an adaptive response to relative hypoxia (13).…”
Section: Reviewmentioning
confidence: 98%
“…This therapeutic effect of metformin is consistent with the result from a reduction in mean glucose levels and/or the slow decline of aging glomerular filtration rate. Several studies have revealed a significantly higher risk of ESA use in association with hyperinsulinemia and insulin resistance 31 . Metformin is known to correct hyperinsulinemia and insulin resistance, resulting in an association with preventing erythropoietin‐secreting cells from being damaged by hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Aminoglycosides are one of the commonest causes of drug‐induced nephrotoxicity 27,28 and long‐term use of aspirin may increase the risk of renal failure 29 . Both ACE inhibitors and ARBs are widely used in patients with renal failure for treating hypertension, though these drugs may decrease erythropoietin formation by inhibiting angiotensin II production and decreasing plasma erythropoietin concentrations, thereby inducing anemia before renal failure 30,31 . The usage of metformin was divided into 3 sections, according to the number of patients.…”
Section: Methodsmentioning
confidence: 99%